The Concept of Slow Living in the Qur’an: A Thematic Study of “Itsmun” and Learning Errors - Vachruddin, Vrisko Putra; Alawy, Muhammad Fahmi (HERMENEUTIK : Jurnal Ilmu al-Qur'an dan Tafsir, 2025)
The position of teachers and students, who position themselves as human beings, cannot be separated from the concept of mistakes and sins committed intentionally or unintentionally. This refers to the Prophet's Hadith which states that every descendant of the Prophet Adam has certainly committed sin. Likewise, in the learning process, in order to understand the meaning of slow living (a peaceful life), a teacher must understand the mistakes in learning that occur between teachers and students, which can lead to sin between them. These mistakes need to be minimized by teachers and students by understanding the forms of error patterns in learning based on the thematic interpretation of the word itsmun in the verses of the Qur'an. This study uses a qualitative research type with a literature review research method and text analysis techniques. The word itsmun in the Qur'an is interpreted as a person who is sinful, an infidel, a liar, and each verse contains the meaning of opposing Allah and the Messenger and has a negative effect on oneself and others. The meaning of mistakes in learning made by teachers and students can be categorized as minor or major sins. In addition, in general, the categories of teacher and student mistakes are more directed towards human sins against the rights of society and the environment, as well as sins against oneself. The meaning of the phrase "itsmun" relates to the concept of slow living, which involves using time effectively and efficiently to achieve learning goals. Its connection to learning theory emphasizes the professionalism of teachers as role models for students, helping them avoid sinful behavior. Posisi guru dan murid yang menempatkan diri sebagai sosok manusia maka tidak akan terlepas dari konsep kesalahan maupun dosa yang diperbuat secara sengaja maupun tidak. Hal tersebut mengacu pada Hadis Nabi yang menyatakan bahwa setiap keturunan Nabi Adam pasti pernah melakukan dosa. Begitu pun dalam proses pembelajaran, guna memaknai slow living (kehidupan yang tenang) maka seorang guru harus memahami kesalahan dalam pembelajaran yang terjadi antara guru dan murid sehingga muncullah dosa diantara keduanya. Kesalahan tersebut perlu diminimalisir oleh guru dan murid dengan mengetahui bentuk pola kesalahan dalam pembelajaran berdasarkan tafsir tematik lafadz itsmun dalam ayat-ayat al-Qur’an. Penelitian ini menggunakan jenis penelitian kualitatif dengan metode penelitian literature review serta teknik analysis teks. Kata Itsmun  dalam al-Qur’an ditafsirkan sebagai orang yang banyak dosa, orang kafir, kebohongan serta setiap ayat mengandung makna melawan Allah dan Rasul serta memiliki efek negatif terhadap diri sendiri dan orang lain. Makna kesalahan dalam pembelajaran yang dilakukan oleh Guru maupun Murid dapat dikategorisasikan pada kategori dosa kecil atau besar. Selain itu secara umum kategori kesalahan Guru dan Murid lebih mengarah pada dosa manusia terhadap hak-hak masyarakat dan lingkungan serta dosa terhadap diri sendiri. Keterkaitan makna lafadz itsmun dengan konsep slow living ialah pada pemanfaatan waktu secara efektif dan efisien dalam mencapai tujuan pembelajaran. Sedangkan keterkaitannya dengan teori pembelajaran ialah menekankan profesionalisme guru sebagai panutan bagi murid untuk menghindari perbuatan-perbuatan dosa.